Delirium as a mediating factor in the survival benefits of dexmedetomidine in acute brain injury management - Juan Wang; Jia-qing Sun; Yue Lu; Qi-lin Yang; Peng-lai Zhao; Chun-Hua Hang; Wei Li (Scientific Reports)
Abstract Acute brain injury (ABI) is a leading cause of ICU admission and mortality. Effective sedation is essential for preventing secondary brain injury, and dexmedetomidine has emerged as a potential neuroprotective agent. We conducted a retrospective analysis using the MIMIC-IV v3.1 database, including adult patients admitted to the ICU with ABI. Patients were divided into two groups based on whether they received dexmedetomidine. Propensity score matching (PSM), weighting methods, and doubly robust estimation were used to adjust for confounding factors. Results from the doubly robust analysis showed that dexmedetomidine use was significantly associated with reduced in-hospital mortality (HR: 0.41, 95% CI: 0.35–0.48, p < 0.001) and ICU mortality (HR: 0.34, 95% CI: 0.28–0.41, p < 0.001). Additionally, dexmedetomidine was associated with significantly increased vasopressor-free days (MD: 2.64, 95% CI: 1.98–3.30, p < 0.001) and ventilation-free days (MD: 2.23, 95% CI: 1.59–2.86, p < 0.001). Further mediation analysis indicated that delirium mediated 37% of the effect of dexmedetomidine on in-hospital mortality and 60% of its effect on ICU mortality. This suggests that delirium may be a key mediator of dexmedetomidine’s beneficial effects, consistent with its potential advantages in sedation and neuroprotection observed in previous studies. In conclusion, dexmedetomidine use in ICU patients with ABI is associated with significantly lower mortality and improved clinical outcomes, with delirium acting as a critical mediator.